Consumer Attitudes towards Household Waste Sorting - Fröhlich, Aleš; Branská, Lenka; Paták, Michal; Pecinová, Zuzana (Česká společnost průmyslové chemie, 2021)
Manufacturers of consumer chemicals have been endeavouring in recent years to increase the sustainability of their product packaging. They apply various strategies, in particular reduce, reuse and recycle. The recycle strategy presupposes the cooperation of final consumers. The role of final consumers in relation to the recycling process and household waste sorting has not yet been addressed in the literature. Therefore, a primary quantitative research was conducted among 350 users of consumer chemicals aimed at finding out their attitudes to individual activities in the sorting of household waste. It was found that consumers' willingness to engage in these activities varies, also depending on the classification characteristics of the respondents (gender, age, education, income level and form of housing). A critical group in terms of willingness to sort the waste are university-educated young high-income men living in flats.
Postoje spotřebitelů k třídění odpadů z domácnosti
Keywords: packaging; consumer chemicals; attitudes to the sorting of household waste; obaly; spotřební chemie; postoje obyvatel; třídění komunálního odpadu